Effect of endophytic Fusarium oxysporum on paralysis and mortality of Pratylenchus goodeyi - Mwaura, P.; Dubois, T.; Losenge, T.; Coyne, Danny L.; Kahangi, E. (2010)
Three bioassays were conducted to investigate the antagonistic effect of secondary metabolites produced by 5 endophytic Fusarium oxysporum isolates from banana (Musa spp.) plants in Kenya, against Pratylenchus goodeyi. Percentage paralyses were recorded 3, 6 and 24 h after exposure to culture filtrates. Percentage mortality was evaluated after 48 h. All isolates caused significantly higher percentage paralysis (17.5 - 25.9%) and percentage mortality (62.3 - 72.8%) of P. goodeyi motile stages compared to the control (8.4 - 10.9% and 17.3 - 34.6%, respectively). Percentage paralysis of motile stages of P. goodeyi decreased as the length of time exposure to culture filtrates increased, while mortality increased as length of nematodes exposure to culture filtrates increased. Kenyan isolates performed equally as good as the Ugandan isolate (V5W2) in causing paralysis and mortality. Results from this study demonstrated that endophytic F. oxysporum antagonizes P. goodeyi through production of secondary metabolites.